1995
DOI: 10.1038/nsb0295-96
|View full text |Cite
|
Sign up to set email alerts
|

What do dysfunctional serpins tell us about molecular mobility and disease?

Abstract: Proteinase inhibitors of the serpin family have a unique ability to regulate their activity by changing the conformation of their reactive-centre loop. Although this may explain their evolutionary success, the dependence of function on structural mobility makes the serpins vulnerable to the effects of mutations. Here, we describe how studies of dysfunctional variants, together with crystal structures of serpins in different forms, provide insights into the molecular functions and remarkable folding properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
351
1
8

Year Published

1996
1996
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 421 publications
(366 citation statements)
references
References 100 publications
6
351
1
8
Order By: Relevance
“…In contrast to previous descriptions of the heparin binding site (1,12,13,(25)(26)(27)(28), we found that Lys 39 , Arg 46 , Arg 132 , Lys 133 , Lys 136 , and Lys 275 contribute minimally to ATIII affinity for heparin. Thus, as a whole, our data establish that basic residues in close proximity to each other exhibit distinct interactions with heparin and imply that a geometrically precise configuration of positive charges is required for heparin binding to ATIII.…”
Section: Fig 1 Atiii Variant Interactions With Heparin and Thrombincontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast to previous descriptions of the heparin binding site (1,12,13,(25)(26)(27)(28), we found that Lys 39 , Arg 46 , Arg 132 , Lys 133 , Lys 136 , and Lys 275 contribute minimally to ATIII affinity for heparin. Thus, as a whole, our data establish that basic residues in close proximity to each other exhibit distinct interactions with heparin and imply that a geometrically precise configuration of positive charges is required for heparin binding to ATIII.…”
Section: Fig 1 Atiii Variant Interactions With Heparin and Thrombincontrasting
confidence: 55%
“…Based on genetic variant, chemical modification, glycosylation isoform, and structural data, a cluster of positively charged residues in the helix D region has been proposed to interact with essential, negatively charged sulfate and carboxylate groups on heparin and to form the heparin binding site of ATIII (1,12,13,25). Specific interactions of ATIII and the pentasaccharide have also been proposed based on docking studies using cleaved antithrombin structures (26 -28).…”
mentioning
confidence: 99%
“…In this case, Met 358-Ser 359 cleavage would be an absolute requirement for inhibition and the inhibited proteinase would exist with its catalytic serine acylated by the a-carbonyl of Met 358 (Lawrence et al, 1995;Wright & Scarsdale, 1995). Others have concluded that cleavage may be a result of the denaturing conditions required to visualize it and that the observed acylation (SDS-stable complex formation) is an artifact and equivalent to a trapped intermediate in the substrate hydrolysis pathway (Travis & Salvesen, 1983;Longstaff &Gaffney, 1991;Mast et al, 1991;Stein & Carrell, 1995). In this case, the serpins would be more like the standard mechanism inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The serpin fold contains 9 a-helices and 3 @-sheets, describing a scaffold that is significantly larger and more complex than those of the standard mechanism inhibitors (Loebermann et al, 1984;Stein & Carrell, 1995). The latter have a rather rigid RSL, which the binding cleft of target proteinases accommodates without any major conformational rearrangements (Read & James, 1986; Bode & Huber, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation